The Philosophical Meaning of Nyolat Traditional Ceremony as Local Wisdom: Forms of Anthropological Representation of the Dayak Tribe Uud Danum - Riko, Albertus (Universitas Tanjungpura, 2025)
The Nyolat traditional ceremony is a form of culture as a system that becomes a habitus in the Uud Danum Dayak community. This habitus has existed for a long time by the ancestors and until now it has become a culture that has always been maintained. Changing times are indeed recognized as a challenge to the existence of maintaining that ancestral tradition. However, this is not a reason to eliminate a culture that has been rooted since ancient times. Its uniqueness as one of the traditions becomes its own uniqueness as the local wisdom of the indigenous Dayak Uud Danum community. The philosophical meaning or symbol of the message that is about to be expressed becomes the fruit of the philosophical reflection of humans wanting to express their relationship with nature and Mohotalak (God). Also at this level, the Nyolat traditional ceremony, which is a symbol and uniqueness for the Uud Danum Dayak community, is an important part of seeing a deeper correlation to human death. This means that humans do not only reach death, but after humans die, they will experience a further pilgrimage to eternal Betang (Heaven) to unite with Mohotalak (God). On the same occasion, the expression in the form of representation of the Nyola traditional ceremony is a form of expression of love for the family, accompanying or praying for their deceased relatives so that they will receive forgiveness and be accepted in the presence of the Existing One of all that is.